Epidermal overexpression of transgenic ΔNp63 promotes type 2 immune and myeloid inflammatory responses and hyperplasia via NF‐κB activation. Issue 3 (February 2014) - Du, Jihui; Romano, Rose‐Anne; Si, Han; Mattox, Austin; Bian, Yansong; Yang, Xinping; Sinha, Satrajit; Van Waes, Carter; Chen, Zhong
Abstract ΔNp63 is known to be critical in skin development and cancer; however, how it triggers proliferation and inflammation in vivo remains to be elucidated. Here, we find that induced ΔNp63 expression in skin of transgenic mice (TG) results in a hyperproliferative epidermis coupled with inflammatory infiltrates. In situ, infiltrating cells include CD45+ leukocytes, CD19+ B lymphocytes, CD3+ T lymphocytes, CD4+ T helper, CD25+/Foxp3+ Treg, Ly6B+ neutrophils, S‐100+ dendritic cells, and macrophages bearing CD11b+, F4/80+, CD68+, and CD206+ M2 type markers. Transcriptional profiling of TG skin revealed increased gene expression involved in inflammation and immune responses, including Th2/M2 cytokines and chemokines. These genes were co‐regulated by ΔNp63 and NF‐κB RelA or cRel, and enhanced by TNF‐α. Elevated cRel, RelA, and IKKs were observed in TG mouse skin and human squamous carcinomas with ΔNp63 overexpression. Thus, our findings unveil a missing link connecting overexpressed ΔNp63 with aberrant NF‐κB activation, pro‐inflammatory and type 2 cytokines and chemokines, and host infiltrates during skin inflammation and hyperplasia. Our findings provide a missing link between ΔNp63 overexpression and NF‐κB‐mediated inflammation, of potential relevance to the pathogenesis of squamous carcinoma. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.